(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Women are the indispensible part of a society. Theireducation influence the coming generation. The development of future generationmainly depends upon the education of women section .So the education of womenis realized to be the most essential part for the development of the society.It can help every woman to educate their children to be good manager of thefamily as well as the active member of the society. The children learn theirmanners and behavior at home and mostly mothers are responsible for cultivatinggood behavior in their children .Every educated woman can run her house welland make it a paradise on earth .Every educated woman can think well about herfuture and her aim in life and then choose the appropriate subject which willbe useful to her throughout the life. In a democratic system the position ofwomen is equal with that of men .Nowadays women are also conscious about theirrights and obligations.